2010
DOI: 10.1007/s11033-010-9954-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Bacillus lipase by directed evolution for enhanced thermal stability: effect of isoleucine to threonine mutation at protein surface

Abstract: A lip gene from a Bacillus isolate was cloned and expressed in E. coli. By thermal denaturation analysis, T(1/2) of lipase was observed to be 7 min at 50°C with less than 10% activity after 1 h incubation at 50°C. To expand the functionality of cloned lipase, attempts have been made to create thermostable variants of lip gene. A lipase variant with an isoleucine to threonine amino acid substitution at the protein surface was isolated that demonstrated higher thermostability than its wild type predecessor. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Here, substitution of structural Lys173 with Ala increased both activity and thermostability of the lipase variant. These results support the concept that activity and thermostability could be independent properties of enzymes [Khurana et al, 2011]. Figure 8 a illustrates the effect of different organic solvents on lipase activity.…”
Section: Biochemical Characteristicssupporting
confidence: 81%
See 4 more Smart Citations
“…Here, substitution of structural Lys173 with Ala increased both activity and thermostability of the lipase variant. These results support the concept that activity and thermostability could be independent properties of enzymes [Khurana et al, 2011]. Figure 8 a illustrates the effect of different organic solvents on lipase activity.…”
Section: Biochemical Characteristicssupporting
confidence: 81%
“…In some cases, simultaneous improvement of thermostability and enzyme activity were obtained [Khurana et al, 2011;Kolling et al, 2010], while findings to the contrary have been reported in other studies [Patkar et al, 1998;Sharma et al, 2014]. Here, substitution of structural Lys173 with Ala increased both activity and thermostability of the lipase variant.…”
Section: Biochemical Characteristicsmentioning
confidence: 62%
See 3 more Smart Citations